Frequency of Ischemic Mitral Regurgitation in ST Elevation Myocardial Infarction and Its Impact on Hospital Course - Nouman Khan, Muhammad Shafique Arshad, Abat Khan, Muhammad Omer Hashmi, Taskin Ahmad Khan Rathore, Nabil Younas, (Pakistan Journal of Medical & Health Sciences, 2023)
Background and Aim: Ischemic mitral regurgitation (IMR) is the most prevalent complication following myocardial infarction (MI) and coronary artery disease. Acute or chronic MI can lead to IMR resulting from an abnormality in regional wall motion or dysfunction of papillary muscles in a territory with structurally normal mitral valve leaflets, coronary artery disease and chordae tendineae. The present study aimed to determine the incidence of ischemic mitral regurgitation in ST elevation myocardial infarction and its impact on hospital course. Material and Methods: This cross-sectional study was conducted on 164 myocardial infarction patients in the Department of Cardiology of Pakistan Institute Medical Sciences Hospital, Islamabad over a time period of 6 months. Institute research and ethical committee approved the study protocol. Patients with prior mitral surgery, heart failure, previous myocardial infarction, and mitral valve disorders were excluded. Demographic detail, echocardiographic parameters, and myocardial complications were recorded. Other parameters such as Killip class, in-hospital mortality, and MI territory with respect to electrocardiographic changes were recorded. Data analysis was carried out in SPSS version 26. Results: Of the total 164 MI patients, there were 114 (69.5%) male and 50 (30.5%) females. The overall mean age was 58.62±8.62 years. The incidence of IMR was 106 (64.6%), out of which the prevalence of mild, moderate, and severe MR were 86 (81.1%), 12 (11.3%), and 8 (7.6%) respectively. No significant association was found between the presence of IMR and other parameters such as diabetes, smoking, hypertension, gender, and BMI. There was a significant association between triglyceride and serum LDL-cholesterol levels with IMR presence. On comparing the IMR and no MR cases, left ventricular ejection fraction reduced but pulmonary arterial pressure increased in IMR groups. Conclusion: The present study found that the prevalence of IMR was 64.6% among MI patients and approximately half of the patients who suffer from IMR after having an AMI experience complications as a result of it. A proper treatment decision depends on assessing the severity of the MR in relation to AMI complications. Keywords: Ischemic mitral regurgitation, Myocardial infarction, ST elevation